Stress, stressors, and stress management practices among public-school teachers - Mañas, Jonathan Lapuz; Ang, Roel Sanchez (International Journal of Public Health Science (IJPHS), 2025)
Stress manifests differently among individuals in various circumstances, stemming from multiple sources. Teachers, in particular, encounter many stressors from personal and work-related domains. This study examines the stress levels of elementary, junior high school, and senior high school public school teachers within Congressional District IV of the Division Office of Nueva Ecija, focusing on everyday life stressors. Additionally, it investigates the stress management practices they employ for coping. The personal metrics of these teachers were analyzed to ascertain their significant relationship with stress levels. Data were randomly collected from 273 respondents through a questionnaire developed by Villamayor. The study unveils that public-school teacher experience slight stress levels and utilize diverse stress management techniques to tackle these stressors. However, the personal metrics of respondents were found to have an insignificant relationship with their stress levels. Nevertheless, the findings of this study pave the way for developing a comprehensive stress management plan to assist public school teachers.